Numerical CFD Simulation Flow of Radial Impellers in Reactor Tanks for Durian Peel Synthesis: พลศาสตร์ของไหล, ใบพัดกวนแบบ radial impellers, การกระจายของอนุภาคของแข็ง - Piya, Ibroheng -; Puzu, Ni-oh (Princess of Naradhiwas University Journal, 2019)
This research investigated flow of alkalization reaction for the synthesis of suspended durian peels mixed in NaOH solution. The experiment of reaction generated circulation flow using 100 rpm speed motor when radial impellers stirred the reactor diameter 230 mm and installed baffles four pieces. The propeller distances from bottom of reactor tank were set at 0.1D and 0.2D in order to investigate flow patterns. laser Induced Fluorescence, LIF, technique was used to detect and capture the distribution of particles. Flow simulation method from the ANSYS Fluent software, which validate from experimental result, was also employed to examine the flow pattern that distribute particles of suspended thoroughly in the reactor. This study revealed that the experiment which was conducted with a propeller which was 0.1D height showed the distribution of particles, which was better than that of flow distribution at 0.2D. This result was offered by greater presenting of axial and radial speed flow.